Risk of surgical site infection and efficacy of antibiotic prophylaxis: A cohort study of appendectomy patients in Thailand - Kasatpibal N. (2014)
Background: No data currently exist about use of antibiotics to prevent surgical site infections (SSI) among patients undergoing appendectomy in Thailand. We therefore examined risk factors, use, and efficacy of prophylactic antibiotics for surgical site infection SSI among patients with uncomplicated open appendectomy. Methods: From July 1, 2003 to June 30, 2004 we conducted a prospective cohort study in eight hospitals in Thailand. We used the National Nosocomial Infection Surveillance (NNIS) system criteria to identify SSI associated with appendectomy. We used logistic regression analysis to obtain relative risk estimates for predictors of SSI. Results: Among 2139 appendectomy patients, we identified 26 SSIs, yielding a SSI rate of 1.2 infections/100 operations. Ninety-two percent of all patients (95% C1, 91.0-93.3) received antibiotic prophylaxis. Metronidazole and gentamicin were the two most common antibiotic agents, with a combined single dose administered in 39% of cases. In 54% of cases, antibiotic prophylaxis was administered for one day. We found that a prolonged duration of operation was significantly associated with an increased SSI risk. Antibiotic prophylaxis was significantly associated with a decreased risk of SSI regardless of whether the antibiotic was administered preoperatively or intraoperatively. Compared with no antibiotic prophylaxis, SSI relative risks for combined single-dose of metronidazole and gentamicin, one-day prophylaxis, and multiple-day antibiotic prophylaxis were 0.28 (0.09-0.90), 0.30 (0.11-0.88) and 0.32 (0.10-0.98), respectively. Conclusion: Single-dose combination of metronidazole and gentamicin seems sufficient to reduce SSIs in uncomplicated appendicitis patients despite whether the antibiotic was administered preoperatively or intraoperatively. © 2006 Kasatpibal et al; licensee BioMed Central Ltd.